Y=-5(2x-3)

Simple and best practice solution for Y=-5(2x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y=-5(2x-3) equation:


Simplifying
Y = -5(2x + -3)

Reorder the terms:
Y = -5(-3 + 2x)
Y = (-3 * -5 + 2x * -5)
Y = (15 + -10x)

Solving
Y = 15 + -10x

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Simplifying
Y = 15 + -10x

See similar equations:

| =0+10-8+2 | | 4p/7=7-9+6 | | 3a+7=4 | | 5x-11-4x+24=5 | | u-9=4u+15 | | 16x^6+8x^6=0 | | y=x^2-4x-60 | | 10-2n=3n-20 | | m(n)=m+n | | -6v=-12b | | 29=33.3+7 | | 0=ln(2x+5)*ln(9x^2) | | 8-2n-14=-27-9n | | 1.8x=0.9 | | -27=8+7x | | 45s=121 | | 4y+4x=-4 | | 27=8+7x | | a-5=8 | | 5x-7+4y+3=180 | | 120+0.60p=60+0.90p | | y=(x^2)+6x | | 8+2a=-2a-16 | | 8n-4=3n+6 | | (x^2-25)(9x+1)=0 | | 17=-2d-14 | | 11a=-16+7a | | 7x=10+6x | | 11a=-16+7w | | .25a+4=.75a+8 | | 96+4c=-44c | | 0.5x-7=-4 |

Equations solver categories